Adsorption of Cd2+ and Pb2+ on Agricultural Byproducts - Jahagirdar, D.V.; Nigal, J.N. (Asian Journal of Chemistry, 2010)
Adsorption of toxic metal ions like Cd2+ and Pb2+ on different vegetable and agricultural byproducts were measured at room temperature by atomic absorption spectrophotometric (AAS) and differential pulse polarography (DPP) methods. The adsorption of Cd2+ follows the order polymerised onion skin > bagasse > banana husk > suffola husk > spinach; whereas the adsorption of Pb2+ follows the order polymerised onion skin > spinach > suffolahusk > bagasse > banana husk. Polymerised onion skin shows maximum adsorbing capacity for both the ions compared to other adsorbents. The adsorption due to raw onion skin is almost equal to polymerised onion skin. Therefore it can be suggested that raw onion skin is a better substitute for polymerised onion skin. Also the raw onion skin would be a more inexpensive adsorbent than the one modified by a polymer.